Scoring first and home advantage in the NHL - Jones, M. B. (International Journal of Performance Analysis in Sport, 2009)
Home advantage in the NBA has recently been reported to be "frontloaded," that is, it is largest in the 1st quarter, smallest in the 4th quarter, and in-between in the 2nd and 3rd quarters. Home advantage in the 1st quarter was 60% of home advantage at the end of the game. The present study was intended to determine if NHL hockey, a very different sport, is also frontloaded. The results were that home advantage in the first goal was 53.01% (home wins) and 52.37% in goals scored after the first. Home advantage in complete games was 56.05%. Hence, the advantage accumulated in the 1st quarter equaled 49.75% of the advantage in complete games. Theories of "psychological momentum" have been advanced according to which scoring first gives a team an advantage in subsequent play. In the NHL, however, no such advantage obtains. In fact, the team scored against does slightly better in goals scored after the first than the team which scores first. Momentum theory also claims that scoring first markedly increases the likelihood of winning. It does, but the effect is due mainly to the fact that the first goal is included in the final score.